Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/tox.23344
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR‐497‐5p inhibits cell apoptosis and promotes autophagy in Parkinson's disease by upregulation of FGF2

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder with increasing prevalence in elderly individuals globally. MicroRNAs (miRNAs) have been confirmed to participate in the pathogenesis of various neurodegenerative diseases, including PD. MiR‐497‐5p is previously reported to be upregulated in PD. The present study was designed to further explore the function of miR‐497‐5p in PD. MiR‐497‐5p was significantly upregulated in 1‐methyl‐4‐phenylpyridinium (MPP+)‐treated SH‐SY5Y cells. Inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…23,35 Former studies have proven the promoting role of miR-497-5p in neuronal apoptosis induced by MPP + and ketamine (an anesthetic). 24,36 Herein, it was found that miR-497-5p level in SH-SY5Y cells was upregulated by BV treatment in a dose-dependent manner. In addition, further investigation demonstrated that SNHG12 negatively regulated miR-497-5p and alleviated BVinduced neuronal damage in SH-SY5Y cells through interaction with miR-497-5p.…”
Section: Discussionmentioning
confidence: 92%
“…23,35 Former studies have proven the promoting role of miR-497-5p in neuronal apoptosis induced by MPP + and ketamine (an anesthetic). 24,36 Herein, it was found that miR-497-5p level in SH-SY5Y cells was upregulated by BV treatment in a dose-dependent manner. In addition, further investigation demonstrated that SNHG12 negatively regulated miR-497-5p and alleviated BVinduced neuronal damage in SH-SY5Y cells through interaction with miR-497-5p.…”
Section: Discussionmentioning
confidence: 92%
“…Aberrant expression of miR-497-5p is mainly seen in different types of cancer [41], diabetic nephropathy [42], Parkinson's disease [43], preeclampsia [44], and metabolic syndrome [45]. In particular, Zhao et al have found that miR-497-5p can promote osteoblast differentiation in osteoporosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblots were visualized using the ECL amplification system. Western blot data were quantified using ImageJ software, and relative intensities were calculated to the value of β‐actin 28,29 …”
Section: Methodsmentioning
confidence: 99%